1988
DOI: 10.1016/0041-008x(88)90261-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of an in vitro system to study the effects of lead on astrocyte-endothelial cell interactions: A model for studying toxic injury to the blood-brain barrier

Abstract: We investigated the effect of inorganic lead on the interaction of immature rat astrocytes and bovine adrenal endothelial cells. The two cell types were cultured alone and in coculture in the presence or absence of lead acetate for up to 1 week. A battery of cell specific markers was used for cell identification. Newborn Sprague-Dawley rat brain astrocytes were more sensitive than bovine adrenal endothelial cells to the cytotoxic effects of 10-50 microM lead acetate, as demonstrated by a decrease in cell numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Moreover, clusters of microglial cells were observed at low, noncytotoxic MeHgCl concentrations in 3D cell cultures (Monnet-Tschudi et al, 1996), whereas it occurred only at cytotoxic MeHgCl concentration in purified microglial cell cultures. Such changes in sensitivity to a neurotoxicant have already been described in different cell culture systems, when cultures of one cell type were compared to mixed cell cultures (Wu and Tiffany-Castiglioni, 1987;Gebhart and Goldstein, 1988;Zurich et al, 1998;Mateu et al, 2000;Katsuki et al, 2001) Taken together, the present results indicate that the microglial activation observed in 3D brain cell cultures after noncytotoxic treatment with MeHgCl may be due at least in part to a direct effect of MeHgCl on microglial cells. Clusters of activated microglial cells, formed in response to MeHgCl in a histotypic environment, may interact with neighboring astrocytes, leading to a local increase of IL-6.…”
Section: Discussionmentioning
confidence: 47%
“…Moreover, clusters of microglial cells were observed at low, noncytotoxic MeHgCl concentrations in 3D cell cultures (Monnet-Tschudi et al, 1996), whereas it occurred only at cytotoxic MeHgCl concentration in purified microglial cell cultures. Such changes in sensitivity to a neurotoxicant have already been described in different cell culture systems, when cultures of one cell type were compared to mixed cell cultures (Wu and Tiffany-Castiglioni, 1987;Gebhart and Goldstein, 1988;Zurich et al, 1998;Mateu et al, 2000;Katsuki et al, 2001) Taken together, the present results indicate that the microglial activation observed in 3D brain cell cultures after noncytotoxic treatment with MeHgCl may be due at least in part to a direct effect of MeHgCl on microglial cells. Clusters of activated microglial cells, formed in response to MeHgCl in a histotypic environment, may interact with neighboring astrocytes, leading to a local increase of IL-6.…”
Section: Discussionmentioning
confidence: 47%
“…This is in line with a previous study of Selvin-Testa et al (1991), who also showed an increase of GFAP immunoreactivity following early postnatal lead exposure. Reactive gliosis following lead exposure is not a primary reaction of astrocytes to the toxin; in cultures of both immature and mature astrocytes, lead exposure did not induce a reactive gliosis (Holtzman et al 1987;Gebhart and Goldstein 1988;Tiffany-Castiglioni et al 1989;Tiffany-Castiglioni 1993). The primary response of astrocytes to lead is characterized by uptake and storage of the heavy metal intracellularly (Holtzman et al 1982(Holtzman et al , 1987TiffanyCastiglioni et al 1986).…”
Section: Discussionmentioning
confidence: 96%
“…10) Lead-a well-known neurotoxic heavy metal-induces cerebral edema and cerebellar hemorrhage via a dysfunction of the blood-brain barrier in the brain of exposed humans and animals, [10][11][12][13] suggesting that the abnormality of blood vessels may cause secondary degeneration of the neurons. Although a similar mechanism is possible in the pathogenesis of MeHg-induced neuropathy in the brain, the toxicity of MeHg to blood vessels has been unclear.…”
Section: Discussionmentioning
confidence: 99%